Long‐Term Prognosis of Ischemic Stroke in Young Adults—A Single‐Center Chinese Cohort Study - Yuhui Sha; Qiqi Wang; Mingyu Tang; Ming Yao; Yicheng Zhu; Lixin Zhou; Jun Ni (Brain and Behavior)
ABSTRACT Introduction Young patients with ischemic stroke often present with more complex etiologies and risk factors, making their long‐term prognosis particularly challenging. This study aims to investigate the long‐term prognosis and identify factors associated with recurrent ischemic cerebrovascular events and unfavorable functional outcome in a prospective, single‐center cohort. Methods We consecutively enrolled young adults (aged 18–49) with ischemic stroke in the single‐center cohort at Peking Union Medical College Hospital (PUMCH) from March 2017 to March 2023. Follow‐up was conducted through face‐to‐face visits or telephone interviews. Main outcomes were recurrent ischemic cerebrovascular events and unfavorable functional outcome (an mRS score ≥ 2). Kaplan–Meier analysis was used to estimate the 5‐year cumulative recurrence risk, and multivariate logistic analysis was used to identify predictors of recurrent ischemic cerebrovascular events and unfavorable functional outcome. Results A total of 226 patients (median (IQR) age, 35 (30–41) years; 148 male (65.5%)) were included to the final analysis. According to the TOAST classification, large‐artery atherosclerosis was identified as the most common subtype (38.1%). The 5‐year cumulative recurrence rate for ischemic cerebrovascular events was 13.5% (95% CI: 6.7%–19.9%), with no significant difference between patients with different etiologies. Low education level (OR 12.016, 95% CI: 2.805–51.469, p < 0.001), previous TIA (OR 9.594, 95% CI: 2.500–36.824, p < 0.001), previous ischemic stroke (OR 3.177, 95% CI: 1.128–8.946, p = 0.029), and mRS score at follow‐up (OR 3.339, 95% CI: 1.714–6.502, p < 0.001) were independent risk factors of ischemic cerebrovascular event recurrence after adjusting for sex and age. Baseline mRS scores was identified as an independent predictor of long‐term poor functional outcome (OR 2.264, 95%CI: 1.207–4.246, p = 0.011) after adjusting for sex, age, receiving antiplatelet treatment and having recurrent ischemic stroke or TIA. Conclusions Young patients with ischemic stroke were at risk of recurrent ischemic cerebrovascular events, enhancing the need to enhance stroke prevention and treatment, particularly among young Chinese individuals with low education levels.